Centro de investigación y jardín botánico, barrio Aeropuerto - Acosta Enríquez, Margarita Alejandra (2018)
Starting from the urban plan developed in the project workshop VII 2018-1, the creation of a Research Center and Botanical Garden in the current Bicentennial Park is proposed, this project is destined to the investigation of botany in Quito and its conservation, the function of this equipment is to regenerate an ecosystem that was damaged by the presence of the airport for more tan 50 years. The project is based on two types of architecture, the tectonics which is presented in the greenhouses and the stereotomic that is located in the blocks of laboratories, auditorium, classrooms and administrative. The equipment in two is divided for its operation, the research center as a private block, which only allows the access of the researchers and from where the conservation and the greenhouses are controlled; In the other hand the Botanical Garden of public character consists of a large central block which is freely accessible to give continuity to the fl ows of the park and connect the main pedestrian fl ow that is related to the intermodal station of the Metro, beside it a block with controlled access that has coffee shop fl oor, exhibition areas and herbal fl oor and interactive science area, a third block with auditorium, and a fourth block of classrooms, workshops and offi ces, these blocks have controlled Access The project due to its typology must handle different microclimates, such as laboratories and conservation area, within the latter depending on the greenhouse are divided into four microclimates based on the thermal fl oors of Quito, paramo, cold, medium and warm, the architecture meets every microclimate from its conception, both formally, functionally and technologically.